2022
DOI: 10.3389/fpsyg.2021.784372
|View full text |Cite
|
Sign up to set email alerts
|

Shorebirds’ Longer Migratory Distances Are Associated With Larger ADCYAP1 Microsatellites and Greater Morphological Complexity of Hippocampal Astrocytes

Abstract: For the epic journey of autumn migration, long-distance migratory birds use innate and learned information and follow strict schedules imposed by genetic and epigenetic mechanisms, the details of which remain largely unknown. In addition, bird migration requires integrated action of different multisensory systems for learning and memory, and the hippocampus appears to be the integration center for this task. In previous studies we found that contrasting long-distance migratory flights differentially affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 140 publications
0
6
1
Order By: Relevance
“…In contrast to our results, previous studies on blackbirds revealed relationships of habitat urbanization level with polymorphisms at both of these genes, although they were relatively weak (Mueller et al, 2013). ADCYAP1 was also reported to associate with migratory propensity, distance and restlessness in birds (de Almeida et al, 2022;Mueller et al, 2011). Similarly, relationships between DRD4 gene polymorphism and exploratory behaviour were found in several passerine bird species (e. g. Garamszegi et al, 2014;Mueller et al, 2014) co-regulate gene expression, than in coding gene regions, where non-silent mutations introduce alterations in protein structure.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, previous studies on blackbirds revealed relationships of habitat urbanization level with polymorphisms at both of these genes, although they were relatively weak (Mueller et al, 2013). ADCYAP1 was also reported to associate with migratory propensity, distance and restlessness in birds (de Almeida et al, 2022;Mueller et al, 2011). Similarly, relationships between DRD4 gene polymorphism and exploratory behaviour were found in several passerine bird species (e. g. Garamszegi et al, 2014;Mueller et al, 2014) co-regulate gene expression, than in coding gene regions, where non-silent mutations introduce alterations in protein structure.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, in this work we are pioneers in establishing a method to classify astrocytes based on their morphology changes in response to injury, correlating different morphological parameters with their intensity of the response. Previous works have introduced this type of approaches to study neuronal subpopulations for example in the nucleus of the solitary tract (Schweitzer et Renehan, 1997) or to categorize diverse subpopulations of hippocampal astrocytes in migratory birds (Carvalho-Paulo et al, 2018;Henrique et al, 2021;de Almeida et al, 2022), reactive microglia in models of encephalitis (de Sousa et al, 2015;da Silva Creão et al, 2021) or in models of neuroinflammation (Fernández-Arjona et al, 2017); and immune cells in starfishes (Karetin, 2021). Here, we developed a multimodality index (MMI) to select parameters that best describe the population heterogenicity, and subsequently applied hierarchical clustering (HC), and principal component analysis (PCA) to identify and construct a dendrogram of reactive responses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, several authors have questioned the suitability of the Mantel test in such applications (Guillot & Rousset, 2013; Legendre, Fortin & Borcard, 2015) as this test is designed to compare two distance matrices that both measure differences rather than physical distance and argued that geographic distance expressed in kilometres may exaggerate the relationship. Other potential confounding issues include the post‐hoc grouping of study individuals based on observed outlier status (Bazzi et al ., 2015) or sex (Dor et al ., 2011) rather than predetermined grouping, small sample sizes (de Almeida Miranda et al ., 2022), and the averaging of alleles in heterozygotes to analyse mean allele length (Zhang et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (de Almeida Miranda et al ., 2022) assessed diversity within Adcyap1 in several species of shorebirds: the collared plover, Charadrius collaris (Vieillot), semipalmated sandpiper, Calidris pusilla (Linnaeus), semipalmated plover, Charadrius semipalmatus (Bonaparte), and spotted sandpiper, Actitis macularius (Linnaeus). They found several alleles for each species but the study was limited in its resolution by small sample sizes.…”
Section: Systematic Review Of Published Studiesmentioning
confidence: 99%